Thrombotic vs. Bleeding Events of Interruption of Dual Antiplatelet Therapy within 12 Months among Patients with Stent-Driven High Ischemic Risk Definition following PCI. (13th January 2022) - Wang, Hao-Yu; Xu, Bo; Song, Chen-Xi; Guan, Chang-Dong; Xie, Li-Hua; Zhao, Yan-Yan; Cai, Zhong-Xing; Yuan, Sheng; Dou, Ke-Fei
Abstract : Background . There is a paucity of real-world data regarding the clinical impact of dual antiplatelet therapy (DAPT) interruption (temporary or permanent) among patients at high ischemic risk. The aim of this study was to assess the risk of cardiovascular events after interruption of DAPT in high-risk PCI population. Methods . This study used data from the Fuwai PCI registry, a large, prospective cohort of consecutive patients who underwent PCI. We assessed 3, 931 patients with at least 1 high ischemic risk criteria of stent-related recurrent ischemic events proposed in the 2017 ESC guidelines for focused update on DAPT who were free of major cardiac events in the first 12 months. The primary ischemic endpoint was 30-month major adverse cardiac and cerebrovascular events, and the key safety endpoints were BARC class 2, 3, or 5 bleeding and net adverse clinical events. Results . DAPT interruption within 12 months occurred in 1, 122 patients (28.5%), most of which were due to bleeding events or patients' noncompliance to treatment. A multivariate Cox regression model, propensity score (PS) matching, and inverse probability of treatment weighting (IPTW) based on the propensity score demonstrated that DAPT interruption significantly increased the risk of primary ischemic endpoint compared with prolonged DAPT (3.9% vs. 2.2%; Cox-adjusted hazard ratio (HR): 1.840; 95% confidence interval (CI): 1.247 to 2.716; PS matching-HR: 2.049 [1.236–3.399]; IPTW-adjusted HR: 1.843 [1.250–2.717]). This difference was driven mainly by all-cause death (1.8% vs. 0.7%) and MI (1.3% vs. 0.5%). Furthermore, the rate of net adverse clinical events (4.9% vs. 3.2%; Cox-adjusted HR: 1.581 [1.128–2.216]; PS matching-HR: 1.639 [1.075–2.499]; IPTW-adjusted HR: 1.554 [1.110–2.177]) was also higher in patients with DAPT interruption (≤12 months), whereas no significant differences between groups were observed in terms of BARC 2, 3, or 5 bleeding. These findings were consistent across various stent-driven high-ischemic risk subsets with respect to the primary ischemic endpoints, with a greater magnitude of harm among patients with diffuse multivessel diabetic coronary artery disease. Conclusions . In patients undergoing high-risk PCI, interruption of DAPT in the first 12 months occurred infrequently and was associated with a significantly higher adjusted risk of major adverse cardiovascular events and net adverse clinical events. 2017 ESC stent-driven high ischemic risk criteria may help clinicians to discriminate patient selection in the use of long-term DAPT when the ischemic risk certainly overcomes the bleeding one.